An Archetypal Reading of The Arabian Nights: Mythic Hero and Monomyth in Selected Stories (KEMANUSIAAN The Asian Journal of Humanities, 2024)
The Arabian Nights is a literary masterpiece that has captivated readers for centuries with its magical elements, mythical creatures and traditional patterns of archetypes. This study delves into the underlying similarities and differences among the types of archetypal characters depicted in two tales, “Three Apples” and “Ali Baba and the Forty Thieves”. The focus is on the notion of mythic hero, exploring the use of archetypal symbols, images, characters and protagonists’ quests to identify the principles of heroism central to their characterisation. The study draws upon Joseph Campbell’s theory of Monomyth, which entails a pattern for the hero’s journey that includes three rites of passage: separation, initiation and return. By examining the journeys of Ja’far and Ali Baba through this lens, we find that both possess essential qualities of a hero in accordance with the tenets of monomyth. Despite their idiosyncratic differences, they are portrayed as ordinary men without any supernatural heroic powers who are urged to reclaim their social status by embarking on an adventure where they go through rebirth, face death and triumph over evil. The findings highlight how the use of mythical elements such as magic and traditional patterns contribute to the perennial appeal of the collection.